Beyond Neighborhoods and Crime: Expanding the Scope of Social Disorganization to Explain Occupational Deviance1. Issue 2 (30th December 2014) - Davis, Jason; Holland‐Davis, Lisa
Abstract : This article proposes a structural explanation for the occupational deviance dimension of white collar crime. The systemic model of social disorganization theory is used as a framework for understanding organizational conditions that produce high rates of occupational deviance. The model of workplace disorganization proposed here posits parallel mechanisms can be found in communities as well as organizations. Marginalized workplaces, employee turnover, and employee heterogeneity are antecedent factors that discourage employee network formation and collective action against deviance. By refocusing on organizational factors, we offer a broader understanding of occupational deviance, one that can predict and explain the workplace conditions under which counterproductive behaviors occur.